IMPLEMENTASI KEBIJAKAN DISIPLIN PEGAWAI NEGERI SIPIL PADA BALAI BAHASA PROVINSI RIAU TAHUN 2023 - Madali, Muhammad Ryandi Putra Budi; Asrida, Wan (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
Civil Servants, hereinafter referred to as ASN, according to Law Number 94 of 2021 concerning Civil Servant Discipline, are tasked with implementing policies determined by authorized government officials and providing services to the community according to their respective fields. This research wants to find out how the Civil Servant discipline policy will be implemented at the Riau Province Language Center in 2023. This research aims to describe the implementation of Republic of Indonesia Government Regulation No. 94 of 2021 concerning Civil Servant Discipline at the Riau Province Language Center. The regulation explains that obeying obligations and avoiding prohibitions is one of the important points that must be of concern to all civil servants, apart from of course regarding the imposition of disciplinary penalties. This research is descriptive research with a qualitative approach. The types of data are primary data and secondary data, primary data is obtained directly from informants. Meanwhile, secondary data is data that supports or strengthens primary data. Data collection techniques were carried out using interviews and documentation. The data analysis technique used is 4 stages, namely data collection, data reduction, data presentation and conclusion drawing. The results of this research show that the implementation of the Civil Servant Discipline Policy at the Riau Province Language Center has not run optimally, there is a lack of firmness in giving sanctions to civil servants who violated and there are still many civil servants who still violate these regulations. The results of the content research after being analyzed using Edwards George III's Policy Implementation theory show that there are many deficiencies in the discipline of the Civil Servants of the Riau Province Language Center, especially absenteeism and attendance. The Riau Province Language Center has not fully implemented Government Regulation Number 94 of 2021 regarding the imposition of sanctions. Keywords: Implementation, Policy, Discipline.